Maternally supplied S-acyl-transferase is required for crystalloid organelle formation and transmission of the malaria parasite - Santos, Jorge M.; Duarte, Neuza; Kehrer, Jessica; Ramesar, Jai; Avramut, M. Cristina; Koster, Abraham J.; Dessens, Johannes T.; Frischknecht, Friedrich; Chevalley-Maurel, Séverine; Janse, Chris J.; Franke-Fayard, Blandine; Mair, Gunnar R. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Transmission of the malaria parasite from the mammalian host to the mosquito vector requires the formation of adequately adapted parasite forms and stage-specific organelles. Here we show that formation of the crystalloid - a unique and short-lived organelle of the Plasmodium ookinete and oocyst stage required for sporogony - is dependent on the precisely timed expression of the S-acyl-transferase DHHC10. DHHC10, translationally repressed in female Plasmodium berghei gametocytes, is activated translationally during ookinete formation, where the protein is essential for the formation of the crystalloid, the correct targeting of crystalloid-resident protein LAP2, and malaria parasite transmission.
Gesehen am 08.05.2020